Pancreatic pseudocyst and complicated internal hernia. A case report - Miguel Licea Videaux; Iván Ulises Palacios Morejón; Orlando Zamora Santana; Josué Vázquez Arizmendi; Richard Juan Chacón Melcón (Medisur, 2023)
Internal hernias are mostly congenital causes. They constitute rare nosological entities. The acute abdominal picture secondary to the complication of these is related to intestinal occlusion and necrosis. Sometimes, some diseases that precede or are discovered during the clinical condition, such as pancreatic pseudocyst, can make a positive diagnosis difficult. The clinical case of a patient diagnosed with a pancreatic pseudocyst, who presented a complication of internal hernia during the course of the disease it is described in this report. The 45-years-old patient with a pancreatic pseudocyst diagnosis presented symptoms of abdominal pain accompanied by vomiting during his admission, which led to suspicion of rupture of the pseudocyst. He underwent emergency surgery, and evidence of an internal hernia (not diagnosed preoperatively) complicated with small bowel segment necrosis was then obtained. No rupture of the pancreatic pseudocyst was observed. The clinical manifestations of complicated internal hernia and pancreatic pseudocyst rupture are difficult to distinguish from each other. Emergency surgical treatment is the fundamental pillar in the face of diagnostic doubt or clinical worsening of the patient.